Pengaruh Kinerja Keuangan, Struktur Modal Dan Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Good Corporate Governance Sebagai Variabel Moderasi - Ritali Evi Mudrikah; Mulyani Mulyani; Jhon Eferdy (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Every company owner will show potential investors that his company is the right investment alternative, therefore the company owner will give a good signal about the company. Data collection is used as secondary data. The data was tested using statistical analysis, namely using SPSS computer software. The population of this research is manufacturing industrial companies listed on the Indonesia Stock Exchange in 2021 - 2023. The total sample is 26 companies with a total of 78 annual report publications in 2021 - 2023. The analysis method used is the multiple linear regression method. Based on the results of the hypthosts test, it can be concluded that: 1) Financial performance, Capital Structure and Corporate Social Responsibility (CSR) have no effect on company value. 3) Good Corporate Governance (GCG) which is proxied by Managerial Ownership cannot moderate the relationship between financial performance and capital structure on company value in the manufacturing business during the Indonesian Stock Exchange year 2021 – 2023. 4) Good Corporate Governance (GCG) which is proxied by Ownership Managerial management can moderate Corporate Social Responsibility (CSR) on company value in manufacturing companies on the Indonesia Stock Exchange 2021 - 2023.